Removal of copper using seaweed - Nur Syazwani, Mohd Khir (2019)
Investigation of seaweed as bioabsorbtion of heavy metal recently have been popular among researchers due to its effectiveness in removal heavy metal from wastewater. Five marine macroalgae namely, Sargassum Polycystum sp. (Brown),Kappa Stratum sp. (Red),Euchema Spinosum sp.(Red), Kappa Alverezir sp (Red), and Caulerpa Lentifera sp.(green) were screened for their metal uptake capacities for Cu at various initial concentrations 10, 20, 30, 40 and 50 mg/L and variable contact period 5 to 300 minutes. The cu uptake value in the different species were in the order of Euchema Sphinosum sp.> Sargassum Polycystum sp. > Caulerpa Lentifera sp. > Kappa Alverezi sp. > Kappa Stratum sp. The effect of contact time, pH and adsorbent dosage were studied. The values of Freundlich model constants (1/n ranged from 0.1253 and 0.1962) and Langmuir isotherm indicated good biosorption.